Korupce jako ekonomický jev a její vliv v ČR a SR - Pellešová, Pavlína (Univerzita Pardubice, 2009)
Paper analyses the corruption by means of an index of corruption perception. The Czech Republic and Slovak Republic are from the beginning of transformation process evaluated not very positively. The Governmental Strategy for the Fight against Corruption during 2006 – 2011 and set the principles of the battle against corruption aiming to withdraw the main causes of corruption.
Keywords: Corruption; Corruption Perception Index; Transparency International